Dor de mãe: lutos possíveis e impossíveis das vítimas da violência urbana - Fedri, Bruno Cervilieri (2014)
This study was aimed at assessing, through psychotherapeutic session records and interviews, the differences in the mourning process of two mothers whose children were fatal victims of urban violence in the city of São Paulo. In psychotherapy sessions, it was found that some mothers had greater difficulty in dealing with the violent loss of their children in relation to other mothers, posing questions related to the possibility and impossibility of mourning. Therefore, two mothers who had differences in the relationship with the lost son were chosen: one in which the mother reapplied attention and interest in other activities and objects, rather than the mother who showed no interest in other elements and objects unless the lost son. To develop this point, studies of urban violence in the city of São Paulo, considerations about the place of the psychoanalyst in the assistance to victims of violence and the profile of the victims were raised, followed by studies related to death and dying as a way to demarcate social and inherent cultural aspects to the subject. Related traumatic neurosis studies were also performed according to the clinical examination of the case, from the Freudian notions of mourning and melancholy to the Winnicott s theory of personal maturation. From this study, it can be concluded that the possibility of dealing with the loss of a child is conditioned to emotional achievements related to the stage of concern, being the failure of this achievement related to the impossibility of the mourning process